Synthesis and reactivity of magnetically diverse Au@ Ni core-shell nanostructures - Bharathan, Vysakh A.; Raj, Govind K.; Joy, Pattayil Alias; Vinod, Chathakudath P. (Particle & Particle Systems Characterization, 2014)
Core-shell bimetallic Au@Ni nanoparticles, with gold cores and thin nickel shells with overall size less than 10 nm, are synthesized and stabilized in pure cubic (fcc) and hexagonal (hcp) phase. Due to their unique crystal, electronic, and geometric structure, they show interesting magnetic and chemical properties. The Au@Ni-fcc is magnetic, whereas Au@Ni-hcp is non-magnetic. Both the bimetallic nanostructures are stable to surface oxidation until 150 degrees C and show excellent catalytic activity for p-nitrophenol reduction reaction.
Keywords: Au-Ni nanoparticles; bimetallic nanostructures; magnetic core-shell nanoparticles; oxidation resistance

Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P. (ChemistrySelect, 2016)
Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10-15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8-10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C-C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts.
Keywords: Bimetallic nanoparticles; Gold catalysis; hydrogenation reactions; synergistic effects